Technological method for increasing residual compressive stress of aluminum alloy bar and application

By performing small deformation drawing processing on aluminum alloy rods, the problem of stress corrosion cracking caused by residual stress generated by aluminum alloy rods during processing is solved, and the residual tensile stress is converted into compressive stress is achieved, which improves the material's stress corrosion resistance.

CN119776744AActive Publication Date: 2025-04-08CENT SOUTH UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411762696.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-04-08
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

The residual stress generated by aluminum alloy rods during processing will cause stress corrosion and cracking, affecting their application in aerospace and automotive fields. The prior art is difficult to effectively and easily eliminate or transform these residual stresses.

Method used

The aluminum alloy extruded blank is pre-stretched by drawing processing. The surface of the rod is plastically deformed by drawing by small deformation, and the internal stress is redistributed, thereby generating residual compressive stress in the axial direction.

Benefits of technology

The diameter of aluminum alloy rods is effectively reduced, and the residual tensile stress is converted into residual compressive stress, reducing the risk of stress corrosion cracking and improving the material's stress corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005168099100000071
    Figure BDA0005168099100000071
  • Figure BDA0005168099100000081
    Figure BDA0005168099100000081
  • Figure BDA0005168099100000091
    Figure BDA0005168099100000091
Patent Text Reader

Abstract

The invention discloses a technological method for increasing residual compressive stress of an aluminum alloy bar and application. The technological method comprises the steps that the aluminum alloy bar is quenched and drawn after being subjected to solution treatment; the accumulated deformation of drawing is not higher than 15%. According to the technological method for increasing the residual compressive stress of the aluminum alloy bar, an aluminum alloy extrusion blank is pre-stretched through a drawing machining method, and the internal stress state of the aluminum alloy extrusion blank can be changed and redistributed. And small-deformation drawing is selected, so that plastic deformation is only generated on the surface of the bar during drawing, shrinkage of the surface layer of the bar is internally limited, and therefore, residual compressive stress exists on the surface layer of the bar in the axial direction.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum alloys, and in particular to a process method for increasing the residual compressive stress of an aluminum alloy bar and an application thereof. Background Art

[0002] As a lightweight, high-strength, corrosion-resistant material, aluminum alloy is widely used in the field of aerospace fasteners, such as bolts, screws, nuts, rivets, etc., and has become an indispensable component of aerospace structures. However, with the increasing technical requirements, the requirements for the performance of aluminum alloys are also constantly increasing. Due to the composition characteristics of Al-Zn-Mg-Cu alloy, it shows a relatively high sensitivity to stress corrosion cracking (SCC). The number of fasteners such as bolts and nuts used in an aerospace aircraft ranges from hundreds of thousands to millions, and their total weight can account for 5-6% of the total weight of the aircraft. When aluminum alloy fasteners are used in aerospace vehicles, stress corrosion cracking often occurs, and they cannot be used safely, efficiently and safely. Residual stress is a key factor affecting the stress corrosion performance of aluminum alloys. Studies have shown that residual compressive stress can reduce the tendency of stress corrosion cracking of samples, while residual tensile stress will increase the tendency of stress corrosion cracking of samples. Before processing, aluminum alloy bar blanks generally undergo extrusion forming and subsequent solid solution and quenching aging heat treatment processes. These pretreatment processes will affect the residual stress of the alloy, thereby affecting its stress corrosion resistance. Due to the uneven metal flow during the extrusion deformation process, additional tensile stress is generated on the surface of the extruded material, which will increase the stress corrosion sensitivity of the alloy. Moreover, the alloy needs to be solution treated at a high temperature above 450°C and then quickly quenched. Relevant studies have shown that aluminum alloys produce large residual stress during solution quenching, even close to the yield strength of the material, and this residual stress will also have a significant effect on stress corrosion. Therefore, it is necessary to optimize the bar preparation process to effectively eliminate the surface residual tensile stress or convert it into residual compressive stress. There are currently four main methods for eliminating residual stress:

[0003] The first is natural aging, which eliminates stress by placing it naturally. This method is too time-consuming and often takes months or even years, and has poor production efficiency. The second is the most traditional and popular method - thermal aging, which puts the workpiece into a thermal aging furnace for heat treatment to eliminate stress at high temperature. However, if the aging temperature is low, the residual stress changes very little, while a high aging temperature will lead to a decrease in alloy strength. Therefore, this method is difficult to operate, has strict requirements on equipment and process, and the effect is difficult to guarantee. The third method is to use sub-resonance to eliminate stress. The process parameters of this method are highly dependent on the shape of the workpiece. Different processing parameters need to be compiled for workpieces of different shapes. Complex workpieces must be operated by skilled professional technicians, and only 23% of the workpiece stress can be eliminated. The fourth method is vibration aging to eliminate stress. Through mechanical assembly, a complete set of stress elimination equipment is formed. It can eliminate stress in a short time for the workpiece, covering all workpieces that need to eliminate stress. However, there are still deficiencies in the mechanism of vibration aging process, and there is still controversy at home and abroad as to whether it is suitable for airborne equipment.

[0004] Therefore, it is necessary to propose a process that is simple to operate, highly feasible, and can improve the stress state of aluminum alloy bars. Summary of the invention

[0005] The present invention aims to solve the above-mentioned technical problems existing in the prior art. To this end, the present invention proposes a process method for increasing the residual compressive stress of an aluminum alloy bar. The aluminum alloy extruded blank is pre-stretched by a drawing process, and its internal stress state will change and redistribute. A small deformation drawing is selected so that the drawing only occurs plastic deformation on the surface of the bar, so that the shrinkage of the surface layer of the bar is restricted by the inside, so that the surface layer of the bar in the axial direction is residual compressive stress.

[0006] The present invention also proposes an application of the above process method in the preparation of aerospace components or automobile components.

[0007] According to one aspect of the present invention, a process for increasing residual compressive stress of an aluminum alloy bar is proposed, comprising: subjecting the aluminum alloy bar to solution treatment, followed by quenching and drawing;

[0008] The cumulative deformation of the drawing is not higher than 15%.

[0009] The principle of the present invention is:

[0010] Drawing with small deformation increases the surface residual compressive stress. The residual stress distribution of the bar after drawing has the following three conditions:

[0011] ① During drawing, the entire cross-section of the rod undergoes plastic deformation, residual tensile stress is generated in the outer layer of the rod, and residual compressive stress appears in the center layer.

[0012] ② During drawing, plastic deformation occurs only on the surface of the rod, resulting in residual compressive stress on the surface of the rod and residual tensile stress in the center.

[0013] ③ When drawing, plastic deformation does not enter the center layer of the bar, so the distribution of residual stress of the drawn product should be the middle of the first two cases. The outer layer of the bar after drawing is residual tensile stress, the center layer is also residual tensile stress, and the middle layer is residual compressive stress. In the above three cases, we use a small deformation amount per pass to make the drawing only plastic deformation on the surface of the bar, thereby generating residual compressive stress on the surface of the bar.

[0014] According to the embodiments of the first aspect of the present invention, there are at least the following beneficial effects:

[0015] Compared with the prior art, the beneficial technical effects of the present invention are: ① obtaining the effect of reducing the diameter of the aluminum alloy bar; ② reducing the residual stress of the original aluminum alloy bar, and being able to convert the residual tensile stress into residual compressive stress.

[0016] The present invention mainly aims at the method of increasing the residual compressive stress of aluminum alloy bars, and studies the improvement law of residual stress distribution by drawing process. Compared with extrusion forming, drawing can process thin-walled tubes and very thin materials. The metal undergoes plastic deformation through the die hole to obtain products with the same shape and size as the die hole. Moreover, due to the small friction, the uneven deformation of the drawn products is much smaller than that of the extruded products. Compared with the prior art, the present invention achieves the effect of reducing the diameter of aluminum alloy bars; at the same time, the residual stress of the original aluminum alloy bars is reduced, and the residual tensile stress can be converted into residual compressive stress.

[0017] The aluminum alloy rod of the present invention does not take alloy components into consideration.

[0018] In some embodiments of the present invention, the solutionizing temperature is 350-550°C.

[0019] In some embodiments of the present invention, the solution treatment time is 1 to 5 hours.

[0020] Under the above solid solution conditions, overburning will not occur and the internal structure can reach a uniform solid solution state.

[0021] In some embodiments of the present invention, the quenching method includes water-cooling quenching.

[0022] In some embodiments of the present invention, the water cooling quenching time is no longer than 10 s.

[0023] In some embodiments of the present invention, the drawing comprises multi-pass drawing.

[0024] In some embodiments of the present invention, in the multi-pass drawing, the deformation amount of a single pass is not higher than 10%.

[0025] In some embodiments of the present invention, in the multi-pass drawing, the deformation amount of a single pass is 8-10%.

[0026] In some embodiments of the present invention, the aluminum alloy rod comprises a 7075 aluminum alloy rod.

[0027] In some embodiments of the present invention, the diameter of the aluminum alloy rod is 10 to 20 mm.

[0028] According to another aspect of the present invention, the application of the process method in the preparation of aerospace components or automobile components is proposed. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a metallographic photograph of sample 1 in the test example;

[0030] Figure 2 This is a metallographic photograph of sample 2 in the test example;

[0031] Figure 3 This is a metallographic photograph of the sample drawn to 11.5 mm in Example 1;

[0032] Figure 4 This is a metallographic photograph of the sample drawn to 14 mm in Example 2;

[0033] Figure 5 This is a metallographic photograph of the sample drawn to 11 mm in Comparative Example 1;

[0034] Figure 6 This is a metallographic photograph of the sample drawn to 10 mm in Comparative Example 2. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0036] Example 1

[0037] This embodiment provides a process for increasing the residual compressive stress of an aluminum alloy bar, and the specific steps are as follows:

[0038] In this embodiment, a 7075 aluminum alloy extruded bar with a diameter of 12 mm is selected, and its alloy composition is as follows: Si 0.03, Fe0.11, Cu 2.18, Mn 0.043, Mg2.04, Cr 0.033, Zn 8.06, Ti 0.02, Zr 0.12, and the balance is aluminum;

[0039] S1. Select the original rod of 50cm long with the above composition, turn one end into Φ9mm and the length is 75mm. Firstly, carry out solution treatment at 470℃×60min and water quenching;

[0040] S2. The 7075 aluminum alloy in the solid solution state is deformed to Φ11.5 mm by one pass of cold drawing, and the deformation amount of the pass is 8.16%.

[0041] S3. Finally, the original Φ12mm rod and the sample drawn to Φ11.5mm were used to measure the residual stress on the surface using X-ray diffraction technology.

[0042] After a secondary cold drawing to Φ11.5mm, the residual stress value on the surface of the sample decreased from 48.5MPa of the original bar to a residual compressive stress of -25.54MPa, and the residual stress state changed from tensile stress to compressive stress.

[0043] It can also be seen from the metallographic photos that the deformation degree of the rod is small, the elongation of the grains along the drawing direction is not obvious, and the equiaxed shape of the original billet is basically maintained, which to a certain extent indicates that the plastic deformation has not completely entered the center layer.

[0044] Example 2

[0045] In this embodiment, a 7075 aluminum alloy extruded bar with a diameter of 15 mm is selected, and its alloy composition is as follows: Si 0.12, Fe0.15, Cu 1.62, Mn 0.15, Mg2.49, Cr 0.22, Zn 6.04, Ti 0.025, Zr 0.031, and the balance is aluminum;

[0046] S1. Select the original rod of 50cm long with the above composition, turn one end into Φ9mm and the length is 75mm. Firstly, carry out solution treatment at 470℃×60min and water quenching;

[0047] S2. The 7075 aluminum alloy in the solid solution state is deformed to Φ14 mm by one pass of cold drawing, and the deformation amount of the pass is 12.89%.

[0048] S3. Finally, the original Φ15mm rod and the sample drawn to Φ14mm were used to measure the residual stress on their surface using X-ray diffraction technology.

[0049] This embodiment provides a process method for increasing the residual compressive stress of an aluminum alloy bar. The difference between this embodiment and Embodiment 1 is that a different diameter of the original bar is selected. The Φ15 mm original bar is cold drawn to Φ14 mm in one pass, and the deformation amount in one pass is 12.89%. The residual stress value on the surface of the sample changes from -32.01 MPa of the original bar to -127.92 MPa, and the residual compressive stress increases by about 100 MPa.

[0050] Comparative Example 1

[0051] This comparative example provides a process for increasing the residual compressive stress of an aluminum alloy bar, specifically:

[0052] In this comparative example, a Φ12 mm 7075 aluminum alloy extruded bar is selected, and its alloy composition is as follows: Si 0.03, Fe0.11, Cu 2.18, Mn 0.043, Mg2.04, Cr 0.033, Zn 8.06, Ti 0.02, Zr 0.12, and the balance is aluminum;

[0053] S1. Select a 50cm long original bar, turn one end into Φ9mm and 75mm long, first perform solution treatment at 470℃×60min, and then water-quench;

[0054] S2. The 7075 aluminum alloy in the solid solution state was cold drawn to Φ11.5 mm in the first pass, and the deformation amount was 8.16%;

[0055] S3. The aluminum alloy, which is then drawn and deformed to Φ11.5 mm, is then cold-drawn and deformed to Φ11 mm in the second pass, with a deformation of 8.51% and a cumulative deformation of 15.97%;

[0056] S4. Finally, the X-ray diffraction method was used to measure the residual stress of the Φ11mm drawn bar;

[0057] Comparative Example 1 is based on Example 1 and is subjected to a second cold drawing process to deform the sample to Φ11 mm, while other parameters remain unchanged;

[0058] After two passes of cold drawing, the residual stress value on the surface of the Φ11mm sample decreased from 48.5MPa of the original bar to 36.76MPa, and the residual stress state did not change.

[0059] Comparative Example 2

[0060] This comparative example provides a process for increasing the residual compressive stress of an aluminum alloy bar, specifically:

[0061] In this comparative example, a 7075 aluminum alloy extruded bar with a diameter of 12 mm is selected, and its alloy composition is as follows by mass percentage: Si 0.03, Fe 0.11, Cu 2.18, Mn 0.043, Mg2.04, Cr 0.033, Zn 8.06, Ti 0.02, Zr 0.12, and the balance is aluminum;

[0062] S1. Select a 50cm long original bar, turn one end into Φ9mm and 75mm long, first perform solution treatment at 470℃×60min, and then water-quench;

[0063] S2. The 7075 aluminum alloy in the solid solution state was cold drawn to Φ11.5 mm in the first pass, and the deformation amount was 8.16%;

[0064] S3. The aluminum alloy, which is then drawn and deformed to Φ11.5 mm, is then cold-drawn and deformed to Φ11 mm in the second pass, with a deformation of 8.51% and a cumulative deformation of 15.97%;

[0065] S4. The aluminum alloy, which is then drawn and deformed to Φ11mm, is then cold-drawn and deformed to Φ10mm in the third pass, with a deformation of 17.36% and a cumulative deformation of 30.57%;

[0066] Comparative Example 2 is based on Comparative Example 1 and undergoes a third cold drawing process to deform the sample to Φ10 mm, while other parameters remain unchanged.

[0067] After three cold drawing passes to Φ10mm, the residual stress value on the surface of the sample decreased from 48.5MPa of the original bar to 18.36MPa, and the residual stress state did not change. The metallographic photos show that some slip bands appear in the center layer of the sample bar, indicating that the plastic deformation has entered the center layer from the surface of the bar.

[0068] Test Case

[0069] In this test example, the original bars of the above-mentioned embodiments and comparative examples were sampled and residual stress was tested by X-ray diffraction method. The test results are listed in Table 1 and Table 2:

[0070] Table 1 X-ray diffractometer measurement results of residual stress on the surface of original 7075 aluminum alloy bar

[0071] sample Slope Standard Deviation Residual stress / MPa Sample 1 Φ12mm -0.387 0.312 48.5±27.1 Sample 2 Φ15mm 0.193 0.269 -32.01±19.98

[0072] The residual stress on the surface of the original bar and the drawn sample was obtained by X-ray diffractometer. The incident light was incident at 0°, 5°, 10°, 15°, 20°, 25°, 30°, 35°, 40° and 45° to obtain the peak values ​​of different diffraction angles. The data points with low intensity were discarded and the statistical results were presented in various tables. The slope M is obtained by linear fitting with the peak angle, and then the residual stress value σ=K×M is obtained according to the stress constant K.

[0073] The residual stress value of the original 7075 aluminum alloy extruded bar was determined by X-ray diffraction method to be 48.5 MPa, and the initial state was a tensile stress state.

[0074] Figure 1 This is a metallographic photograph of the original rod 7075 with a diameter of 12 mm for test example sample 1. The original rod 7075 with a diameter of 12 mm has fine grains in the center layer, most of which are equiaxed fine grains.

[0075] Figure 2 This is the metallographic photo of the original bar 7075 with a diameter of 15 mm for test example sample 2. The central grain is a fine grain with a nearly equiaxed shape and a layered morphology with radial stratification;

[0076] Table 2 Surface residual stress of 7075 aluminum alloy after drawing to different diameters

[0077]

[0078] From the data in the analysis table, it can be seen that for the 7075 rod with an original diameter of 15mm, the cumulative deformation is 12.89% when the single-pass drawing is to 14mm, and the residual compressive stress reaches 127.92MPa, and the residual compressive stress increases by about 95MPa; for the 7075 rod with an original diameter of 12mm, the first pass of drawing has the best effect on improving the residual stress, and the residual stress state also changes from the tensile stress of the original rod to compressive stress, and the compressive stress on the surface of the rod reaches 25.54MPa. At this time, plastic deformation occurs only on the surface of the rod, with residual compressive stress on the surface of the rod and residual tensile stress in the center. As the drawing continues, the plastic deformation enters the center layer of the rod, and the residual compressive stress on the surface of the rod decreases significantly, and gradually transforms into residual tensile stress.

[0079] It can be seen that when the cumulative deformation is less than 15%, the drawing process has the best effect in reducing the residual stress of the original aluminum alloy bar, converting the residual tensile stress on the surface of the original bar into residual compressive stress.

[0080] Table 3 Different incident angles Statistical table of diffraction angle θ values ​​under

[0081] serial number φ angle <![CDATA[sin 2 f]]> Peak Angle 1 0 0.000 148.424 2 5 0.008 148.390 3 10 0.030 148.237 4 15 0.067 148.350 5 20 0.117 148.187 6 25 0.179 148.259 7 30 0.250 148.033 8 35 0.329 148.339 9 40 0.413 148.134 10 45 0.500 148.188

[0082] Table 3 corresponds to the test example sample 1 (the original bar in Example 1), the peak value of the 7075 original bar Φ12mm at different diffraction angles was measured by the tilt method, and the effective results were analyzed. The slope was obtained by linear fitting with the peak angle, and then multiplied by the stress constant K=-125.19 to obtain the surface residual stress value of 48.5MPa.

[0083] Table 4 Different incident angles Statistical table of diffraction angle θ values ​​under

[0084]

[0085]

[0086] Table 4 corresponds to the test example sample 2. The peak values ​​of the 7075 original bar Φ15mm at different diffraction angles were measured by the tilt method. The effective results were analyzed. The slope was obtained by linear fitting with the peak angle, and then multiplied by the stress constant K=-165.72 to obtain the surface residual stress value of -32.01 MPa.

[0087] Table 5 Different incident angles Statistical table of diffraction angle θ values ​​under

[0088] serial number φ angle <![CDATA[sin 2 f]]> Peak Angle 1 0 0.000 156.286 2 5 0.008 156.287 3 10 0.030 156.303 4 15 0.067 156.358

[0089] Table 5 corresponds to Example 1. The side tilt method is used to measure the peak values ​​of different diffraction angles of the 7075 bar Φ12mm single-pass drawn to 11.5mm sample. The effective results are analyzed. The slope was obtained by linear fitting with the peak angle, and then multiplied by the stress constant K=-174.02 to obtain the surface residual stress value of -25.54MPa.

[0090] Figure 3 This is a metallographic photograph of a 7075 aluminum alloy bar with a diameter of 12 mm drawn to 11.5 mm in a single pass in Example 1. The center of the bar includes slender grains and some grains elongated along the drawing direction. Some parallel slip bands appear on the surface of the bar, and the plastic deformation of the surface of the bar is obvious.

[0091] Table 6 Different incident angles Statistical table of diffraction angle θ values ​​under

[0092]

[0093]

[0094] Table 6 corresponds to Example 2. The side tilt method is used to measure the peak values ​​of different diffraction angles of the 7075 bar Φ15mm single-pass drawn to 14mm. The effective results are analyzed. The slope was obtained by linear fitting with the peak angle, and then multiplied by the stress constant K=-165.72 to obtain the surface residual stress value of -127.92MPa.

[0095] Figure 4 This is Example 2, the metallographic structure of a 7075 aluminum alloy rod with a diameter of 15 mm after single-pass drawing to 14 mm. The center is a mixture of deformed grains and dynamically recrystallized grains, the white area is the recrystallization area, the surface of the rod is a coarse grain layer, and a small amount of slip bands appear on the surface of the rod, but do not enter the center of the rod.

[0096] Table 7 Different incident angles Statistical table of diffraction angle θ values ​​under

[0097] serial number φ angle <![CDATA[sin 2 f]]> Peak Angle 1 0 0.000 139.158 2 5 0.008 139.105 3 10 0.030 139.091 4 15 0.067 139.073 5 20 0.117 139.056 6 25 0.179 139.043

[0098] Table 7 corresponds to Example 1. The side tilt method is used to measure the peak values ​​of different diffraction angles of the 7075 bar Φ12mm multi-pass drawn to 11mm. The effective results are analyzed. The slope was obtained by linear fitting with the peak angle, and then multiplied by the stress constant K=-174.02 to obtain the surface residual stress value of 36.76MPa.

[0099] Figure 5 For comparative example 1, the metallographic photograph of 7075 aluminum alloy with a diameter of 12 mm and multiple passes drawn to 11 mm shows that more slip bands appear on the surface of the rod and more fine grains appear in the center layer, indicating that dynamic recrystallization has occurred.

[0100] Table 8 Different incident angles Statistical table of diffraction angle θ values ​​under

[0101] serial number φ angle <![CDATA[sin 2 f]]> Peak Angle 1 0 0.000 139.116 2 5 0.008 139.118 3 10 0.030 139.110 4 15 0.067 139.105 5 20 0.117 139.102 6 25 0.179 139.093 7 30 0.250 139.086 8 35 0.329 139.067 9 40 0.413 139.059 10 45 0.500 139.073

[0102] Table 8 corresponds to Example 2. The side tilt method is used to measure the peak values ​​of different diffraction angles of the 7075 bar Φ12mm multi-pass drawn to 10mm. The effective results are analyzed. The slope was obtained by linear fitting with the peak angle, and then multiplied by the stress constant K=-174.02 to obtain the surface residual stress value of 18.36MPa.

[0103] Figure 6 This is a metallographic photograph of a 7075 aluminum alloy with a diameter of 12 mm drawn in three passes to 10 mm. It can be seen that the center of the rod includes slender grains and some recrystallized grains, and parallel slip bands also appear, indicating that the center layer has also undergone strong plastic deformation.

[0104] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A process for increasing residual compressive stress of aluminum alloy bars, characterized in that: include: The aluminum alloy bar is solution treated, then quenched and drawn; The cumulative deformation of the drawing is not higher than 15%.

2. The process according to claim 1, characterized in that: The temperature of the solid solution is 350-550°C.

3. The process according to claim 1, characterized in that: The solid solution time is 1 to 5 hours.

4. The process according to claim 1, characterized in that: The quenching method includes water cooling quenching.

5. The process according to claim 4, characterized in that: The water cooling quenching time is not more than 10s.

6. The process according to claim 1, characterized in that: The drawing includes multiple drawing passes.

7. The process according to claim 6, characterized in that: In the multi-pass drawing, the deformation amount of a single pass is not higher than 10%.

8. The process according to claim 6, characterized in that: In the multi-pass drawing, the deformation amount of a single pass is 8-10%.

9. The process according to claim 5, characterized in that: The diameter of the aluminum alloy rod is 10 to 20 mm.

10. Use of the process according to any one of claims 1 to 9 in the preparation of aerospace components or automobile components.

Citation Information

Patent Citations

  • Control method of surface orange peel effect in second tension forming of high strength aluminium alloy

    CN104711498A

  • Performance optimization method for ultrahigh-strength aluminum alloy blank

    CN111004984A

  • Preparation method of large-size 6061 aluminum alloy plate for semiconductor equipment

    CN112593100A

  • Preparation method of high-strength stress-corrosion-resistant aluminum alloy profile

    CN113136497A

  • Method for increasing circumferential residual compressive stress of extrusion hole and application of method

    CN114535331A